Seminoma with focal gonadoblastoma in anatomically normal male: A rare case report - Sujata S Giriyan; M B Bharati; Nahida Afshan Shigli (Wolters Kluwer Medknow Publications, 2020)
Gonadoblastomas are unusual gonadal neoplasias that frequently appear in dysgenetic gonads. Approximately 80% of patients are phenotypic females and 20% are males. A very high frequency is associated with malignant germ cell tumor. We present a case of 37-year-old normal fertile man with descended testis who presented with swelling and pain in left testis since 6 months. On examination, left testis was swollen, hard, and tender. Ultrasound examination of left testis showed hypoechoic lesion neoplastic with multiple enlarged lymph nodes in pre- and para-aortic region. After high left inguinal orchidectomy, histopathology of specimen showed tumor tissue composed of cells arranged in large nests separated by fibrous stroma infiltrated by lymphocytes with focal area showing nests of cells with vesicular nucleus and moderate amount of eosinophilic cytoplasm with eosinophilic material which was calcified, suggestive of seminoma testis with focal area of gonadoblastoma.